(untitled) (SCIENCE TIME JOURNAL, 2026)
The article examines translation strategies used to convey the idiostyle of A. P. Chekhov in literary translation. The relevance of the study is determined by the complexity of preserving the author’s stylistic features in translation, such as laconic narration, subtext, irony, and colloquial speech. The research material consists of Chekhov’s short stories and their translations. Using comparative, stylistic, and translation analysis methods, the main strategies employed to preserve Chekhov’s idiostyle are identified and systematized. The results demonstrate that lexical and syntactic transformations, as well as compensation strategies, play a decisive role in maintaining the author’s style in translation.